Baby‐led complementary feeding: Randomized controlled study. Issue 12 (25th December 2018) - Dogan, Erkan; Yilmaz, Gonca; Caylan, Nilgun; Turgut, Mahmut; Gokcay, Gulbin; Oguz, Melahat Melek
Abstract: Background: Baby‐led weaning (BLW) is an approach to introducing solid foods to infants that gives control of the feeding process to the infant. Anecdotal evidence suggests that BLW is becoming popular with parents, but scientific research is limited to a few publications. This study assessed growth, hematological parameters and iron intake in 6–12‐month‐old infants fed by traditional or baby‐led complementary feeding. Methods: We recruited 280 healthy 5–6‐month‐old infants allocated to a control (traditional spoon feeding; TSF) group or an intervention (BLW) group in a randomized controlled trial. Infant growth, hematologic parameters and iron intake were evaluated at age 12 months. Results: Infants in the TSF were significantly heavier than those in the BLW group. Mean weight in the BLW group was 10.4 ± 0.9 kg compared with 11.1 ± 0.5 kg in the TSF group. There was no statistically significant difference in the iron intake from complementary foods between the BLW (7.97 ± 1.37 mg/day) and TSF (7.90 ± 1.68 mg/day) participants who completed the diet records. Hematologic parameters were similar at 12 months. The incidence of choking reported in the weekly interviews was not different between the groups. Conclusions: To the best of our knowledge, this is the first randomized ‐controlled study to have examined the impact of weaning method on iron intake, hematological parameters and growth in breast‐fed infants. BLW can be an alternative complementary feeding type without increasing the risk of iron deficiency, choking or growth impairment.